1985
DOI: 10.1530/jrf.0.0740087
|View full text |Cite
|
Sign up to set email alerts
|

Effects of abdominal vagotomy on serum LH concentrations in female rats

Abstract: Vagotomy on the morning of pro-oestrus did not prevent the pro-oestrous LH surge and rats became oestrous on the following day. However, vagotomized rats then exhibited a period of acyclicity which lasted for 20\m=.\4\m=+-\1\m=.\3 (s.e.m.) days. Food intake and body weight also declined after vagotomy. During the first week after vagotomy, afternoon LH surges generally did not occur, a pattern which was similar in animals pair fed with vagotomized rats. However, pair-fed rats showed oestrous cycles while vagot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…These regions receive input from the vagus nerve [17,[51][52][53]. Integration of signals in the brainstem could then influence the ovaries through either a descending spinal cord projection or more directly through an extraspinal vagal pathway [54,55]. Such pathways may also affect adrenal corticosterone production which is elevated following neurectomy.…”
Section: Discussionmentioning
confidence: 99%
“…These regions receive input from the vagus nerve [17,[51][52][53]. Integration of signals in the brainstem could then influence the ovaries through either a descending spinal cord projection or more directly through an extraspinal vagal pathway [54,55]. Such pathways may also affect adrenal corticosterone production which is elevated following neurectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical vagotomy, i.e., bilateral abdominal (subdiaphragmatic) truncal vagotomy, was performed as previously described [2] with some modification. In short, after cutting skin and muscles from the xiphoid to the navel, the liver was stabilized with ligatures to visualize the subdiaphragmatic vagus nerves.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, ovulation in both ovaries was confirmed 4–6 days after vagotomy treatment, suggesting that the effect of vagotomy on the reestablishment of ovulation is due to the immediate effect that the vagus nerve has on noradrenaline activity in the ovaries rather than the changes in gonadotropin concentration. In this regard, Allen et al (1985) showed that vagotomy on the morning of proestrus did not prevent the proestrus LH surge and rats became estrus on the following day.…”
Section: Discussionmentioning
confidence: 98%